Using cooperative learning to enhance fourth grade students’ speaking skills (2024)
ABSTRACT: This action research investigates the effectiveness of Cooperative Learning to enhance speaking skills. This project was conducted at I. E. Abraham Reyes in a fourth grade group with a low English proficiency. The data was collected through the journals in which I registered all my personal thoughts and reflection, a semi-structured interview with the cooperating teacher (CT) to know her insight about the effectiveness of cooperative learning in the English classroom and a focus group and audio-recording with 12 students to know their experience and perceptions during the implementation of the project. All the data have proved that cooperative learning is a valuable strategy because it boosts students’ confidence, increases motivation and enhancesspeaking skills.